DAMPAK PENAMBANGAN BAHAN GALIAN GOLONGAN C BAGI SOSIAL EKONOMI MASYARAKAT DI KAWASAN ALIRAN BATANG BAYANG KECAMATAN BAYANG - Amrinaldo, Rival; Rianto, M.Pd, Slamet; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (Pendidikan Geografi, 2014)
ABSTRACK             Lack of education and economic conditions of the people that want to get the material easily without considering the environmental damage caused by a dominant factor in the occurrence of mineral mining group C. This study aimed to describe the impact of mining minerals socioeconomic class C for the community in the area of stem flow Kecamtan Bayang . This type of research used in this study is a qualitative analysis research study sites in the flow shadow Trunk, District Bayang. The informants in this study are 32 people covering Wali Nagari, Jorong Mayor, Chairman of Youth, miners and surrounding communities by using the techniques of documentation, observation and interviews. Accuracy of data is tested using the data tringulasi, from the data collected in the analysis of snowball sampling model that consists of data collection, data reduction, data display and conclusion. The results showed that: the impact of mineral mining socioeconomic class C for the people in the District of Bayang Bayang stem flow is (1) Education, public education generally in the flow shadow rod average graduated from elementary and junior high school graduation highest. (2) Eyes search, in general livelihoods as farmers and cut the gum, the result of insufficient livelihoods so that people do a side livelihood. (3) Revenues, Earnings society varies around 135-200 thousand / day and 50-100 thousand / day from the eyes of a side quest. Judging from the level of education and economic conditions of society so rampant mining of minerals category C adult without thinking much about the risk of environmental damage caused.